PEMBELAJARAN CERITA FABEL BERDASARKAN KURIKULUM 2013 PADA SISWA KELAS VII SMP NEGERI 20 PONTIANAK - Mulianti, Citra; Heryana, Nanang; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is motivated by the researcher?s curiosity towards the learning process of fable story based on the 2013 curriculum in the seventh grade students of SMP conducted by the teacher. Project-based learning, frequently asked questions, discussions, and assignments. The purpose of this research is to describe planning, implementation, and evaluation in learning fable story based on curriculum 2013 on VII students of SMPNegeri 20Pontianak Utara.The method in this research is descriptive method with qualitative research form. Data collection techniques used in this study is using direct observation techniques, interviews, and documentation. Based on the results of the study it can be concluded that in the process of learning planning, the implementation of learning fable stories based on the 2013 curriculum in the seventh grade students of SMP Negeri 20 Pontianak Utara is good and in accordance with the curriculum 2013. Studens results in learning fable story is also good. Obtaining knowledge value is 88,65 and skill value is 71,41. Keywords: Learning, fable story, curriculum 2013, descriptive